Validity and reliability of TGMD-2 Surakarta children aged 7-10 years - Ismaryati Ismaryati; Bambang Wijanarko; Islahuzzaman Nuryadin; Rumi Iqbal Doewes; Muhammad Muhyi (Universitas Negeri Malang, 2023)
Motor assessment tests are widely used in many countries, including the Gross Motor Development Test 2 (TGMD-2). TGMD-2 is the most frequently used test to measure children's gross motor development in many countries. The purpose of this research is to be investigated whether TGMD-2 is suitable for measuring gross motor development in Surakarta boys aged 7-10 years. The participants involved in this study were 355 boys aged between 7-10 years, who attended state elementary school. Construct validity was calculated by Exploratory Factor Analysis, and reliability by Cronbach's Alpha. The result of the calculation is average Keyser-Meyer-Olkin (KMO) value is 0.837. This figure indicates that TGMD-2 is good for confirmation purposes. While the reliability is 0.743, categorized as medium. In conclusion, thus it can be concluded that TGMD-2 can used to assess gross motor development of the studied population.